2016
DOI: 10.5812/thrita.31977
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in Children With Otitis Media With Effusion: A Case-Control Study

Abstract: Background: Otitis media with effusion (OME) is one of the main sources of hearing impairment in children. One of the possible causes of middle ear infection and OME is immune system disorders. Based on previous studies, vitamin D deficiency plays an important role in the incidence of middle ear infections. Objectives: This study aimed to determine blood levels of vitamin D in children with OME (as an inflammation of the middle ear) in comparison to a control group of patients admitted to Loghman-Hakim hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The association observed between higher serum 25(OH)D concentration and reduced risk of COME may in part reflect a protective effect of higher serum 25(OH)D concentration on conditions that often precede COME, such as URI and AOM . Episodes of AOM in the last three months put children at a higher risk of developing COME , although OME also frequently occurs independently of AOM .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The association observed between higher serum 25(OH)D concentration and reduced risk of COME may in part reflect a protective effect of higher serum 25(OH)D concentration on conditions that often precede COME, such as URI and AOM . Episodes of AOM in the last three months put children at a higher risk of developing COME , although OME also frequently occurs independently of AOM .…”
Section: Discussionmentioning
confidence: 96%
“…The mean 25(OH)D concentration was lower in the cases; however, the result was not statistically significant and the authors noted that a larger study was needed. Additionally, the cases and controls were all candidates for adenotonsillectomy . No such study has been performed using healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The study was performed among children with adenoid hypertrophy, attempting to evaluate the possible role of vitamin D deficiency in the incidence of SOM through measuring and comparing vitamin D levels in children with and without SOM in two age groups. Several studies have investigated the relationship of low levels of vitamin D with acute otitis media and SOM (27,(29)(30)(31)(32). Some studies have shown similar results in the relationship between SOM and vitamin D without considering age category.…”
Section: Discussionmentioning
confidence: 99%
“…Though the frequency of otitis media with effusion declines with advancing age, other significant contributory factors include parental smoking, recent episodes of upper respiratory tract infections and acute otitis media, parental illiteracy, low socio-economic status, number of siblings and attending daycare facilities. [24][25][26] Birth weight, gestational age and breast feeding also have displayed a significant association. 27 However some older researches have shown a weak correlation with parental smoking, family history of otitis media and parental socioeconomic status.…”
Section: Tympanometrymentioning
confidence: 92%